The Effectiveness of Virtual Reality–Based Training for Family Caregivers in Supporting Post-Stroke Recovery: A Quasi-Experimental Study - Sukron Sukron; Romiko Romiko; Heri Putra; Indah Sari; Muhammad Agung; Muhammad Maulana (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Stroke survivors in low-resource settings often rely on family caregivers to provide essential daily care after hospital discharge. However, many caregivers lack the necessary knowledge, skills, and confidence to perform safe and effective home-based care. Virtual Reality (VR) offers an immersive, interactive, and practical training method that may enhance caregiver preparedness and is associated with improved patient outcomes during post-stroke recovery. This study evaluated the effectiveness of a VR-based caregiver training program on functional, psychological, physiological, and cognitive outcomes among stroke survivors. Methods: A quasi-experimental pre–post design was conducted with 60 caregiver–patient pairs recruited from a community health center in South Sumatra. Participants were assigned to either a VR-based training group or a control group receiving standard discharge education. The intervention consisted of five immersive VR modules simulating stroke-care scenarios, including hygiene, feeding, transfer techniques, positioning, suctioning, and range of motion exercises. Outcome measures included systolic blood pressure, functional independence (Barthel Index), anxiety and depression (HADS), and cognitive status (MoCA). Results: Patients whose caregivers received VR-based training demonstrated significant improvements in patient outcomes compared with the control group. The intervention group showed greater reductions in systolic blood pressure (p = 0.021), increased functional independence (p = 0.041), reduced anxiety (p = 0.017) and depression (p = 0.011), and enhanced cognitive function (p = 0.032). Effect sizes ranged from moderate to large, indicating clinically meaningful improvements. Conclusion: VR-based caregiver training is a feasible, low-cost, and effective strategy associated with improved patient outcomes following caregiver training. Its immersive design provides experiential learning that may support caregiving activities in community health settings with limited resources.